# point out the mistakes $1=2$? [closed]

Q:prove $1=2$ ?

method1:-

let us consider $x=1$

then $x=x^2$

$x-1 =(x^2)-1$

$x-1=(x-1)(x+1)$

$1=x+1$

finally $1=2$

i have little confusion here, is the mistake is considering $x=1$ or else any thing other than this.

method2:-

$-2=-2$

$1-3=4-6$

$(1^2)-(\frac{2*1*3}{2})=(2^2)-(\frac{2*2*3}{2})$

$(1^2)-(\frac{2*1*3}/2)+((\frac{3}{2})^2)=(2^2)-(\frac{2*2*3}{2})+((\frac{3}{2})^2)$

$(1-\frac{3}{2})^2=(2-\frac{3}{2})^2$

$1-\frac{3}{2}=2-\frac{3}{2}$ [here the formula if $x^n=y^n$ then $x=y$ is failed]

$1=2$

point out the mistakes in above two methods exactly and please explain

-

## closed as not constructive by Alex Wertheim, N. S., lab bhattacharjee, Amzoti, MicahJun 13 '13 at 4:58

As it currently stands, this question is not a good fit for our Q&A format. We expect answers to be supported by facts, references, or expertise, but this question will likely solicit debate, arguments, polling, or extended discussion. If you feel that this question can be improved and possibly reopened, visit the help center for guidance.If this question can be reworded to fit the rules in the help center, please edit the question.

possible duplicate of What are some classic fallacious proofs? – lab bhattacharjee Jun 13 '13 at 4:36
We get so many of this question... – Sujaan Kunalan Jun 13 '13 at 4:42

For the first: Don't divide by zero. (That's what you did going from $x-1=(x-1)(x+1)$ to $1=x+1$, since $x=1$.)

For the second: $x^2=y^2$ does not imply that $x=y$. After all, $(-1)^2=1=1^2,$ but $-1\ne 1$. The best we can conclude is that $x=\pm y$.

-
thank you understood – Gangadhar Jun 13 '13 at 4:53

$(1-3/2)^2 = (2-3/2)^2$ does not imply $(1-3/2) = (2-3/2)$. It only implies $(1-3/2) = \pm (2-3/2).$

-

The step $$x - 1 = (x - 1)(x + 1) \implies 1 = x + 1$$

is not valid since $x - 1 = 0$, and division by zero is not allowed. Also,

$$-\frac{1}{2} = 1 - \frac{3}{2} \ne 2 - \frac{3}{2} = \frac{1}{2}$$

-

You have divided by $0$, which is not allowed. (During the step when you divided $x-1$ from both sides.)

-
thank you understood – Gangadhar Jun 13 '13 at 5:54

In the first one you divided by $x-1$, which is illegal cuz $x-1=0$. I don't know what you're doing in the second one but I suspect you also divided by 0 there too lol.

-